2023
DOI: 10.1590/1981-7746-ojs1224
|View full text |Cite
|
Sign up to set email alerts
|

A Educação Permanente em Saúde e os atores do sistema prisional no cenário pandêmico

Abstract: Resumo A Educação Permanente em Saúde legitimou a educação na saúde com base na aprendizagem significativa, em vivências no cotidiano de trabalho e na solução de problemas de forma coletiva, além de estar pautada no Quadrilátero Ensino-Gestão-Atenção-Controle Social. A pandemia da Covid-19 exigiu novas formas de fazer saúde e educação, principalmente no sistema prisional, onde a superlotação é um impeditivo ao isolamento social. Este estudo teve como objetivo identificar, por meio de rodas de conversa virtuais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Our findings suggest that the shortage of qualified professionals is a significant obstacle, representing one of the greatest challenges to containing the spread of COVID-19 in prisons [5]. In line with other studies [23,53], the lack of a primary healthcare team in prison institutions was identified as the main difficulty, resulting in unnecessary escorts and security threats.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings suggest that the shortage of qualified professionals is a significant obstacle, representing one of the greatest challenges to containing the spread of COVID-19 in prisons [5]. In line with other studies [23,53], the lack of a primary healthcare team in prison institutions was identified as the main difficulty, resulting in unnecessary escorts and security threats.…”
Section: Discussionsupporting
confidence: 85%
“…Legislation must recognize the importance of and guarantee access to health care guaranteed, as the implementation of the existing policy is lacking. Permanent health education for workers in the prison system can help professionals recognize PTB in the prison system more quickly and efficiently 20 . Although healthcare access exists in these prisons, there is a failure to passively search symptomatic individuals for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A aprendizagem, enquanto essencial, capacita e possibilita a produção de novos conhecimentos, baseados em situações reais, que são discutidas e analisadas conjuntamente [3,4]. Ely et al (2023) [5], definem que a EPS está alicerçada em quatro pilaresensino, gestão, atenção e controle social. Esses pilares formulam uma estratégia de intervenção associada à formação e desenvolvimento de trabalhadores nas diversas áreas da saúde, incluindo a Odontologia.…”
Section: Introductionunclassified

Educação Permanente em Saúde e a qualidade da assistência odontológica

Victor de Medeiros Martins,
Polline Lacerda Protasio,
Alice da Silva Ferreira
et al. 2023
Sci. Plena